Harvesting chemical information from the Internet using a distributed approach: chemxtreme - Karthikeyan, Muthukumarasamy; Krishnan, S.; Pandey, A. K.; Bender, Andreas (Journal of Chemical Information and Modeling, 2006)
{The Internet is a comprehensive resource of chemical information which is at the same time largely unstructured. It provides a wealth of scientific information such as experimental data and requires a suitable automated data mining and analysis tool for its meaningful exploration. The Java based software presented here, ChemXtreme, is developed for harvesting chemical information from the Internet employing the Google API in combination with a distributed client/server text analysis architecture based on JavaRMI. It represents the first and until now the only toolkit for automated structured data retrieval from the Internet which is itself open source. ChemXtreme employs the ``search the search engine''
Keywords: calcination; clinker; one-dimensional model; rotary cement kiln